Sinergi Pemerintah DPRD dan Masyarakat dalam Perekonomian - Ihsan Rahmadi Wijaya; Muhammad Yafiz (Universitas Dehasen Bengkulu, 2022)
The government as one of the economic actors (government households), has an important function in the economy, which is to function as stabilization, allocation, and distribution. In this case, the role of DPRD to monitor regional finances is very much needed, so that the programs that have been prepared can run effectively, efficiently and economically. The type of research used is qualitative research. The results of this study indicate that the role of the DPRD government in the economy is very significant in the economy.